DYNAMICS OF MELTING IN THE OCEANIC UPPER MANTLE - Perepechko Yu.V.; Sharapov V.N. (My University, 2001)
Convection in the upper mantle has been investigated in the Boussinesq approximation with due regard to four solid-phase transitions above the "perovskite" transition at a depth of 670-700 km for systems of two types: (1) without basaltic crust (some slowly spreading ridges) and (2) with basaltic crust 7 to 20 km thick. Numerical calculations have been carried out on the basis of the method of control volume for a 2D region, 700 × (2500-5000) km2 in size. Development of melting and its extent were estimated on the basis of parameterization of water-free lherzolite according to McKenzie and Niu and Batiza. Mantle rocks melt in systems with initial temperatures exceeding 500°C at a depth of 100 km, 800°C at 300 km, and 1700°C at the upper-lower mantle boundary. At a temperature at the lower boundary below 2000°C, melting proceeds at depths of 24-290 km with the degrees of melting of ~0.05-0.8 15-20 Ma after the beginning of convection and exists for about 20-70 Ma. At a temperature higher than 2000°C, the magmatic system passes through two stages: nonstationary, with the degree of melting of about 0.5-0.6 at depths of ∼30-290 km, and quasi-stationary, with the degree of melting of 0.06-0.4 at depths of ~60-100 km. The horizontal extent of melting zones varies from 150 to 1000 km. A periodical structure forms in the melting zone, and the maximum of melting degree considerably shifts toward the upper boundary of the upper mantle. The velocity of mantle matter near the upper boundary reaches ∼14-25 cm/year before melting, then gradually decreases to 3-9 cm/year by the climax of the magmatic system and to 1.5-2 cm/year by its degeneration. There is no linear relationship between the degree of melting and velocity of the Earth's crust over ascending flows. The thermal flow near the surface of the Earth's crust reaches ~60-145 mW/m2 at maximum melting and decreases to ∼40-60 mW/m2 on degeneration of the magmatic system.